Shocking a CEO: Economic disintegration and executive compensation in manufacturing and services firm - Federico Merchán; Holger Görg (Kiel Institute for the World Economy (IfW Kiel), 2025)
This paper uses the Brexit referendum in 2016 as a quasi-natural experiment to estimate the effect of an exogenous negative shock to globalization on executive compensation for German companies listed in the DAX and MDAX stock indices. We show that it matters whether they work for firms exporting goods or services. The main results indicate that executive compensation in firms operating in sectors that export services was negatively affected, in particular through lower variable compensation. On the contrary, executives of firms that operate in sectors exporting goods were not negatively affected overall, though they experienced a compositional change (from bonuses to equity payments). Sectoral regressions suggest that manufacturing firms redirected successfully exports from the UK to other relevant trade partners, while this was not the case in the service sector.
Keywords: F14; F16; E24; J33; G35; 330; Brexit; executive compensation; dividend; services